Evaluation of Antioxidant and Antimicrobial potential of Leucas urticaefolia (Lamiaceae) - Veena Dixit , Saba Irshad, Priyanka agnihotri, A.K. Paliwal, Tariq Husain (Journal of Applied Pharmaceutical Science, 2015)
The present study was designed to screen phytochemical constituents with antioxidant and antimicrobial activity of 50% EtOH extract of Leucas urticaefolia. Antimicrobial activity was tested against Staphylococcus epidermidis, Salmonella typhi, Salmonella typhimurium, Candida krusei and Aspergillus fumigatus by disc diffusion method. DPPH free radical scavenging assay and ferric reducing assay were used for the determination of antioxidant activity. Qualitative and quantitave analysis of polyphenoles was performed by HPLC-UV. Remarkable antimicrobial potential was exhibited in concentration dependent mode against S. epidermidis, S. typhi and C. krusei. However, S. typhimurium and A. fumigatus showed resistance at lowest concentrations but higher concentrations were effective in inhibiting both microorganisms. Total phelnolic and flavonoid content were found to be 0.71335±0.025% and 0.2594±0.028% respectively. Different concentrations of extract showed dose dependent reducing power and scavenging of DPPH radicals with IC50 149.59±0.24 μg/mL. A marked correlation was observed between antioxidant and antimicrobial activity of 50% EtOH extract of L. urticaefolia. HPLC analysis showed the presence of important polyphenoles and may be attributed to antimicrobial and antioxidant activity of the extract. The observations provided sufficient evidences that L. urticaefolia might indeed be potential sources of natural bioactive agent, if further investigated.
Keywords: Leucas urticaefolia, phenols, flavonoids, Antioxidant, Antimicrobial activity.